Perspectives: Librarian Teaching Identities are Constructed and Contextual: A Case Study of Academic Librarians’ Teaching Identity Development Through a Community of Practice - Sandy, Jillian; Mann, Pamela; VerMeulen, Amanda (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
Drawing inspiration from our own experiences, we find that intentional development of teaching identity through a Community of Practice (CoP) may provide opportunities for librarians’ growth as teachers. The way academic librarians think about teaching identity significantly impacts their effectiveness in the classroom, and the formation of a CoP can yield especially impactful supportive relationships, self-reflective practices, and pedagogical discussions. Through a social learning approach, we recognize the positive impact learning in community can yield; additionally, because of the role of context in teaching, we identify possibilities to address barriers to development of teaching identities. Our focus is on practical application for librarians at any professional stage to use elements of a CoP to cultivate their teaching identity and evolve classroom techniques.